Natural Regeneration Status in Melghat Forests - an overview - Singh, Jarnail; Mahajan, A. G. (Indian Forester, 1998)
Melghat Teak is a valuable genome and it’s wood has unique characteristics of grain mosaic and dark brown heartwood which imparts durability as well as decorativeness to any product prepared from it. An overview provided by regeneration survey reveals that the natural regeneration of Teak is scanty in Melghat forest despite preponderance of seed trees in the overwood. It is apprehended that the paucity of regeneration may result in poor representation of younger age classes in the growing stock and leave the forest in perilously abnormal state. This warrants serious efforts to improve regeneration status so that the lower strata of the forest are adequately replenished with the Teak. The optimality concept for natural regeneration in selection fores has been evolved and on this background a critical assay of the NR problem is made. The problem in Melghat is two faceted - recruitment and establishment. The accountability of seed phenology for poor recruitment and the implications of biotic and ecological factors for the establishment of NR are examined. After reviewing the experience gained by earlier foresters in this field, an innovation is suggested in the present recommendations for pilot trials. The recommendations include identification of "sick grooves" of NR, their revival by boosting as also supplementing the regeneration, selective shrub cutting and heavier types of fellings in the exploitable class.